Coagulation parameters (PT, APTT, INR) as determinants of peri-lesional attenuation and clinical severity in intracerebral hemorrhage: A retrospective analytical study - Saruman, Ardy Ariady; Amran, Muhammad Yunus; Akbar, Muhammad; Zainuddin, Andi Alfian; Sompa, Andi Weri; Rosyidah, Citra (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Intracerebral hemorrhage (ICH) is associated with high mortality and severe neurological disability, largely driven by secondary brain injury such as perihematomal edema (PHE) and hematoma expansion. Abnormalities in coagulation parameters, including prothrombin time (PT), activated partial thromboplastin time (APTT), and international normalized ratio (INR), may be associated with bleeding characteristics and radiological features. Quantitative assessment of peri-lesional attenuation using Hounsfield Unit (HU) values on non-contrast computed tomography (NCCT) provides a practical approach to evaluate tissue changes. This study aimed to investigate the relationship between coagulation parameters, peri-lesional attenuation, and neurological severity measured by the National Institutes of Health Stroke Scale (NIHSS) in patients with ICH. Methods: This study used an analytic observational design with a retrospective approach in patients with primary ICH treated at Dr. Wahidin Sudirohusodo Hospital, Makassar. Data were obtained from medical records, including PT, APTT, and INR values, NCCT findings for HU measurement using a region-of-interest (ROI) method, and NIHSS scores at admission. Statistical analysis was performed to assess relationships between variables, with a significance level of p < 0.05. Results: A total of 150 patients were included, with a predominance of male patients and a mean age of 55.1 ± 15.2 years. A weak but statistically significant association was observed between INR and peri-lesional attenuation. However, coagulation parameters were not significantly associated with neurological severity as measured by NIHSS. Multivariate analysis showed that age and hematoma volume were the main independent predictors of neurological severity. Conclusions: Coagulation parameters show a limited association with peri-lesional attenuation and are not significantly associated with clinical severity in patients with ICH. Clinical and radiological factors, particularly age and hematoma volume, remain the primary determinants of early neurological impairment. Integration of laboratory and imaging findings may support clinical evaluation, although their predictive value for early severity appears limited.